Short-Term Seismic Precursor Anomalies of Hydrogen Concentration in Luojishan Hot Spring Bubbling Gas, Eastern Tibetan Plateau - Zhou, Xiaocheng; Yan, Yucong; Fang, Wenya; Wang, Wanli; Shi, Hongyu; Li, Pengfei (Frontiers in Earth Science, 2021)
The gas compositions (He, H2, CO2, CH4, Ar and N2) and isotope ratios (3He/4He and δ13C) were yearly investigated from April 2010 to April 2019 at the Luojishan spring located in the proximity of the Zemuhe Fault, eastern Tibetan Plateau. The continuous automatic monitoring of hydrogen concentrations in Luojishan hot spring bubbling gas for the purpose of earthquake prediction requires the discrimination of seismic precursor anomalies. Helium isotope ratios (3He/4He) in the bubbling gas of hot springs varied from 0.05 to 0.18 Ra (Ra = 3He/4He = 1.39 × 10−6 in the air), with a maximum mantle-derived He up to 2.2% of the total He measured in the Luojishan hot spring (assuming R/Ra = 8.0 for mantle). This suggests that Zemuhe Fault might act as a conduit for crustal-derived fluid. N2 concentrations in the majority of the hot spring was ≥80 vol%, and δ13CCO2 values varied from −13.2 to −9.3‰ (vs.PDB). Hydrogen concentration time series display a complex temporal pattern reflecting a wide range of different physical processes. There were short-term (5–60 h) seismic precursor anomalies of hydrogen concentration before natural earthquake. The anthropogenically-induced earthquakes provoke only post-earthquake responses. The concentration of hydrogen in bubbling gas of the Luojishan hot spring is sensitive to increase of stress in the Xianshuihe-Xiaojiang fault system. Monitoring the hydrogen concentrations with automatic gas stations may be promising tool for unraveling earthquake mechanisms and for predicting earthquakes.